Iron-copper co-doped graphene composite material, and preparation method and application thereof
Patent Information
- Application Number
- CN202611151038.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-23
AI Technical Summary
然而,光催化效率受制于光生载流子的快速复合、可见光利用率低以及催化剂稳定性不足等问题,仍需进一步优化材料设计与反应体系
本发明提供的铁铜共掺杂石墨烯复合材料的制备方法简单,基于该复合材料的电化学传感器能对0.05 μM~0.5 mM浓度范围内的AP进行灵敏检测,检测限低至0.017 μM,且选择性、稳定性和重现性好。修饰电极作为电化学传感器的敏感元件,将其应用到实际猪肉和牛肉样品中AP的检测,具有良好的检测效果。将FeCu-LIG进一步应用于AP的光催化降解其表现出高效的降解性能,且具有良好的循环使用稳定性和实际水体(自来水、河水)适应性,实现了同一材料体系在AP检测与降解双重功能上的集成应用。
Smart Images

Figure CN122955485A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of graphene composite materials technology, and in particular to an iron-copper co-doped graphene composite material, its preparation method, and its application. Background Technology
[0002] Acetaminophen (AP) is a widely used antipyretic and analgesic drug, commonly used in clinical and veterinary medicine to treat fever, pain, and rheumatism. However, excessive intake can lead to severe liver and kidney damage, and even death. Meanwhile, the overuse of AP in animal husbandry increases the risk of its residues in animal-derived foods. Furthermore, the large-scale production and use of AP has resulted in its frequent detection in natural water bodies (such as surface water and groundwater), soil, and even bottled drinking water, posing a potential threat to the ecological environment and public health.
[0003] Currently, the detection of acrylonitrile (AP) mainly relies on traditional analytical methods such as high-performance liquid chromatography (HPLC), liquid chromatography-tandem mass spectrometry (LC-MS / MS), and gas chromatography (GC). While these methods are accurate and reliable, they often require expensive instruments, complex sample pretreatment, and specialized operation, making them unsuitable for rapid on-site screening. In contrast, electrochemical sensors have attracted significant attention in food safety, biomedicine, and environmental monitoring due to their advantages of high sensitivity, low cost, fast response, and ease of operation. However, the electrochemical response performance of electrode modification materials to the target analyte is crucial, and developing advanced functional materials for electrochemical interfaces has become a key challenge in constructing high-performance AP sensors.
[0004] Given the persistence and ecotoxicity of azophosphorus (AP) in the environment, efficient removal of AP has become a research hotspot in the environmental field. Photocatalysis, due to its advantages such as mild reaction conditions, high mineralization, and no secondary pollution, is widely considered one of the effective ways to degrade organic pollutants. In the photocatalytic process, semiconductor materials are excited by light to generate photogenerated electron-hole pairs, which in turn generate highly oxidizing reactive oxygen species (such as ·OH and ·O2). - Photocatalytic agents (PA) can oxidize and decompose AP molecules into smaller molecule intermediates, which are then mineralized into CO2 and H2O. In recent years, various photocatalytic materials have been used in the photocatalytic degradation of AP, achieving significant progress. However, photocatalytic efficiency is limited by rapid recombination of photogenerated carriers, low visible light utilization, and insufficient catalyst stability, requiring further optimization of material design and reaction systems. Therefore, providing a multifunctional material with both excellent photocatalytic activity and electrochemical sensing performance offers an integrated solution for real-time monitoring and degradation of AP. Summary of the Invention
[0005] In view of this, the present invention aims to provide an iron-copper co-doped graphene composite material, its preparation method, and its application. The modified electrode prepared using FeCu-functionalized LIG as an electrode modification material provided by the present invention exhibits high sensitivity in the portable detection of acetaminophen; simultaneously, the application of this FeCu-functionalized LIG to the photocatalytic degradation of AP also demonstrates excellent catalytic degradation effects.
[0006] To achieve the above objectives, the present invention provides the following technical solution: One of the technical solutions of this invention is a method for preparing an iron-copper co-doped graphene composite material, comprising the following steps: FeCu-MOF was dispersed in an organic solvent to obtain a dispersion; The dispersion was mixed with liquid polyimide and then coated onto the substrate surface, followed by curing to obtain a flexible precursor film. The flexible precursor film was subjected to laser-induced treatment to obtain the iron-copper co-doped graphene composite material.
[0007] The second technical solution of the present invention is an iron-copper co-doped graphene composite material prepared by the above preparation method.
[0008] The third technical solution of the present invention is the application of the above-mentioned iron-copper co-doped graphene composite material in the photocatalytic degradation of acetaminophen.
[0009] The fourth technical solution of the present invention is a modified electrode, wherein the electrode modification material is the above-mentioned iron-copper co-doped graphene composite material.
[0010] The fifth technical solution of the present invention is an electrochemical sensor, comprising the above-mentioned modified electrode.
[0011] The sixth technical solution of the present invention is the application of the above-mentioned iron-copper co-doped graphene composite material, the above-mentioned modified electrode, or the above-mentioned electrochemical sensor in the detection of acetaminophen.
[0012] The present invention discloses the following technical effects: The preparation method of the iron-copper co-doped graphene composite material provided by this invention is simple. The electrochemical sensor based on this composite material can sensitively detect AP in the concentration range of 0.05 μM to 0.5 mM, with a detection limit as low as 0.017 μM, and exhibits good selectivity, stability, and reproducibility. The modified electrode, as the sensitive element of the electrochemical sensor, was applied to the detection of AP in actual pork and beef samples, demonstrating good detection results. Further application of FeCu-LIG to the photocatalytic degradation of AP showed highly efficient degradation performance, good cyclic stability, and adaptability to actual water bodies (tap water, river water), realizing the integrated application of the same material system for both AP detection and degradation. Attached Figure Description
[0013] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0014] Figure 1 Scanning electron microscope (SEM) images of LIG (A and B) and FeCu-LIG (C and D) in the middle; Figure 2 X-ray diffraction (XRD) images of LIG and FeCu-LIG; Figure 3 Cyclic voltammetry (CV) curves of FeCu-LIGE at different laser A powers and B engraving depths; Figure 4 LIGE and FeCu-LIGE in 5.0 mM [Fe(CN)6] containing 0.1 M KCl 3- / 4- CV curve A and EIS curve B in the redox probe solution; Figure 5 CV curves for LIGE, Fe-LIGE, Cu-LIGE, and FeCu-LIGE in 0.1M PBS buffer containing 0.5 mM AP; Figure 6 Figure A shows the CV curves of FeCu-LIGE at different scan rates in 0.1 M PBS buffer containing 0.5 mM AP; Figure B shows the corresponding Ic curves. p and v 1 / 2 The linear relationship between them; C is the redox peak potential (E p ) and the natural logarithm of the scan rate (ln v A linear relationship between them; Figure 7 Figure A shows the linear cyclic voltammetry (LSV) curves of FeCu-LIGE in 0.1M PBS buffer at different pH values containing 0.5 mM AP; Figure B shows the I... p E p Relationship with pH value; Figure 8 LSV curves of FeCu-LIGE with different FeCu-MOF doping amounts in 0.1M PBS (pH 7.0) buffer containing 0.5mM AP; Figure 9LSV curves A and I of FeCu-LIGE in AP solutions of different concentrations p Linear relationship between AP concentration and B; Figure 10 Selectivity assays were performed on FeCu-LIGE by adding 2.5 mM of different interfering agents to 0.1 M PBS (pH 7.0) buffer containing 0.5 mM AP. Figure 11 The stability of FeCu-LIGE in 0.1M PBS (pH 7.0) buffer containing 0.5mM AP was tested for 11 days. Figure 12 Reproducibility tests were conducted on seven different FeCu-LIGE lines in 0.1M PBS (pH 7.0) buffer containing 0.5mM AP. Figure 13 LSV curves of FeCu-LIGE after adding different concentrations of AP to pork A and beef B samples diluted 50 times; Figure 14 In Figure A, LIG, Fe-LIG, Cu-LIG, and FeCu-LIG represent the photocatalytic degradation of AP by LIG, Fe-LIG, Cu-LIG, and FeCu-LIG, and the kinetic fit of the experimental results in Figure B. Figure 15 A represents the effect of the trapping agent on the photocatalytic degradation of AP by FeCu-LIG, and B represents a possible mechanism of photocatalytic degradation of AP. Figure 16 In the figure, A represents the amount of catalyst, B represents the initial concentration of AP, and C represents the effect of pH on photocatalytic degradation performance. Figure 17 Cyclic experiments for the photocatalytic degradation of AP by FeCu-LIG; Figure 18 The graph shows the photocatalytic degradation efficiency of AP in different water samples. Figure 19 This is a schematic diagram illustrating the preparation method and application of the laser-induced iron-copper co-doped graphene composite material of the present invention. Detailed Implementation
[0015] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0016] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0017] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0018] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0019] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0020] Unless otherwise specified, "room temperature" in this invention refers to 25±2℃.
[0021] Laser-induced graphene (LIG) is prepared by a one-step photothermal conversion of a polymer precursor using a laser. In this process, high-energy laser irradiation induces rapid pyrolysis of the precursor, causing carbon atoms to rearrange in situ into a three-dimensional porous graphene network structure. This preparation method requires no catalyst or mask and enables low-cost, large-scale production of patterned electrodes on flexible substrates. The resulting LIG material possesses high porosity, large specific surface area, good conductivity, and mechanical flexibility, providing abundant active sites for subsequent functionalization modifications, which facilitates electron transfer and enhances electrochemical signal transduction.
[0022] Metal-organic frameworks (MOFs), as a class of crystalline materials composed of metal nodes and organic ligands, possess extremely high specific surface area, tunable pore structure, and rich chemical functionality. Laser-induced pyrolysis carbonizes the organic ligands into a three-dimensional porous carbon framework, while the metal nodes are transformed in situ into FeCu nanoparticles, thus constructing a composite structure with high porosity, large specific surface area, and good conductivity. Crucially, the synergistic effect between the reduced bimetallic components (Fe / Cu) is preserved and enhanced after laser treatment: the formation of FeCu and its strong interfacial coupling with the carbon substrate effectively improve the structural stability and electron transport capability of the material; while the interfacial charge rearrangement between the bimetallic components promotes synergistic energy dissipation, further optimizing the electrochemical performance of the material. Therefore, the introduction of FeCu-MOF derivatives can effectively compensate for the shortcomings of the original LIG, such as single component and insufficient sensitivity, providing a feasible strategy for constructing high-performance electrochemical sensing interfaces.
[0023] The first aspect of this invention provides a method for preparing an iron-copper co-doped graphene composite material, comprising the following steps: FeCu-MOF was dispersed in an organic solvent to obtain a dispersion; The dispersion was mixed with liquid polyimide and then coated onto the substrate surface, followed by curing to obtain a flexible precursor film. The flexible precursor film was subjected to laser-induced treatment to obtain the iron-copper co-doped graphene composite material.
[0024] In a preferred embodiment of the present invention, the organic solvent is ethanol; the concentration of FeCu-MOF in the dispersion is 5-50 mg / mL; and the ratio of the dispersion to liquid polyimide is 200 μL: 4 g.
[0025] More preferably, the concentration of FeCu-MOF in the dispersion is 5 mg / mL, 10 mg / mL, 20 mg / mL, 30 mg / mL, 40 mg / mL or 50 mg / mL.
[0026] In a preferred embodiment of the present invention, the curing temperature is 80~100℃ and the time is 20~30min.
[0027] In a preferred embodiment of the present invention, the parameters of the laser-induced treatment are set as follows: wavelength 450nm, laser power 1.38~2.48W, and engraving depth 15%~35%.
[0028] More preferably, the laser power is 1.38W, 1.65W, 1.93W, 2.20W or 2.48W.
[0029] More preferably, the engraving depth is 15%, 20%, 25%, 30%, or 35%.
[0030] A second aspect of the present invention provides an iron-copper co-doped graphene composite material prepared by the above-described preparation method.
[0031] A third aspect of the present invention provides the application of the above-mentioned iron-copper co-doped graphene composite material in the photocatalytic degradation of acetaminophen.
[0032] In this invention, the degradation of acetaminophen is preferably the degradation of acetaminophen in a water sample.
[0033] Furthermore, the initial pH value of the water sample was 3–9.
[0034] The fourth aspect of the present invention provides a modified electrode, wherein the electrode modification material is the above-mentioned iron-copper co-doped graphene composite material (FeCu-LIG).
[0035] The method for preparing the modified electrode in this invention includes the following steps: FeCu-MOF was dispersed in an organic solvent to obtain a dispersion; The dispersion was mixed with liquid polyimide and then coated onto the substrate surface, followed by curing to obtain a flexible precursor film. Based on the pre-designed electrode geometry, the surface of the flexible precursor film is subjected to laser-induced treatment; then, silver paste is coated onto the reference electrode region of the prepared electrode and subjected to thermal curing treatment to obtain the modified electrode.
[0036] The temperature of the thermosetting treatment is 140°C and the time is 20 min.
[0037] A fifth aspect of the present invention provides an electrochemical sensor comprising the modified electrode described above.
[0038] The sixth aspect of the present invention provides the application of the above-mentioned iron-copper co-doped graphene composite material, the above-mentioned modified electrode, or the above-mentioned electrochemical sensor in the detection of acetaminophen.
[0039] In this invention, the detection of acetaminophen is preferably performed on acetaminophen in livestock and poultry meat.
[0040] Furthermore, when detecting AP, FeCu-LIGE was placed in the test sample containing AP, and the electrochemical signal in the test sample was detected by linear cyclic voltammetry (LSV).
[0041] Furthermore, when detecting AP, the concentration of AP solution in the test sample ranged from 0.05 μM to 0.5 mM, and the buffer was 0.1 M phosphate buffer (PBS, pH=7.0); linear cyclic voltammetry (LSV) was used with a potential of 0.1 V to 0.6 V and a scan rate of 0.1 V / s.
[0042] When using the FeCu-LIGE sensor prepared according to this invention to detect AP, the detection range for AP solution is 0.05 μM-0.5 mM, and the detection limit is 0.017 μM.
[0043] Unless otherwise specified, the technical solutions described in this invention are all conventional solutions in the field, and the reagents or raw materials used are all purchased from commercial channels or are publicly available unless otherwise specified.
[0044] The printing silver paste (01L-2210) used in this embodiment of the invention was purchased from Shenzhen Saiya Electronic Paste Co., Ltd.
[0045] The liquid polyimide used in the embodiments of this invention was purchased from Nantong Suyuan Plastics Co., Ltd.
[0046] The FeCu-MOF used in the embodiments of the present invention was prepared according to the method described in "One-pot solvothermal synthesis of Cu-Fe-MOF for efficiently activating peroxymonosulfate to degrade organic pollutants in water: Effect of electron shuttle" Wang Hao et al, Chemosphere, Vol. 352, p. 141333.
[0047] In the comparative examples of this invention, the preparation of Fe-MOF is the same as that of FeCu-MOF, except that the addition of Cu source is omitted.
[0048] In the comparative examples of this invention, the preparation of Cu-MOF is the same as that of FeCu-MOF, except that the addition of the Fe source is omitted.
[0049] To better understand the present invention, the following embodiments further illustrate the content of the present invention, but the content of the present invention is not limited to the following embodiments.
[0050] Example 1 A method for preparing a FeCu-LIGE modified electrode: (1) Preparation of flexible precursor membrane: FeCu-MOF was dispersed in ethanol to prepare a dispersion with a concentration of 30 mg / mL. 200 μL of this dispersion was mixed with 4 g of liquid polyimide. Subsequently, the resulting mixture was coated onto a glass plate and cured in a vacuum oven at 100 °C for 30 min to obtain a uniform and transparent flexible precursor membrane with a thickness of approximately 100 μm.
[0051] (2) Preparation of FeCu-LIGE: Using laser-induced technology, the surface of the prepared flexible precursor film was laser-induced with a semiconductor laser with a wavelength of 450 nm according to the pre-designed electrode geometry. The laser power was 1.38~2.48W (1.38, 1.65, 1.93, 2.20, 2.48W), and the engraving depth was 15%~35% (15%, 20%, 25%, 30%, 35%). Subsequently, the reference electrode area of the prepared electrode was coated with silver paste and cured in an oven at 140℃ for 20 min to obtain the laser-induced iron-copper co-doped graphene composite modified electrode (FeCu-LIGE).
[0052] For comparison, LIGE was prepared as follows: The preparation of LIGE was carried out according to the synthesis method of FeCu-LIGE, but the addition of FeCu-MOF in step (1) was omitted; the remaining steps and parameters were the same as in Example 1; and a laser-induced graphene modified electrode (LIGE) was obtained.
[0053] Example 2 The electrochemical performance of the FeCu-LIGE prepared in Example 1 as the sensing element of an electrochemical sensor was studied: The CV method was used to prepare 5.0 mM [Fe(CN)6] containing 0.1 M KCl. 3- / 4- FeCu-LIGE prepared under different laser parameters (laser power and engraving depth) were tested in a redox probe solution (with a fixed engraving depth of 30% and different laser powers; and with a fixed laser power of 2.20 W and different engraving depths). The FeCu-LIGE exhibited the maximum peak current at a laser power of 2.20 W and an engraving depth of 30%, which represents the optimal laser parameters for FeCu-LIGE preparation.
[0054] Further CV and EIS tests were performed on LIGE and FeCu-LIGE under optimal parameters. The redox peak current of FeCu-LIGE was significantly higher than that of LIGE, and the charge transfer resistance (Rct) was significantly reduced. This phenomenon can be attributed to FeCu accelerating electron transfer on the electrode surface and improving conductivity.
[0055] Example 3 The FeCu-LIGE prepared in Example 1 (FeCu-LIGE prepared under conditions of 2.20W laser power and 30% engraving depth) was used as the sensitive element of the electrochemical sensor. Connected to a portable electrochemical workstation, it can be used as an electrochemical sensor to detect AP. FeCu-LIGE was used as the sensing element of an electrochemical sensor to detect AP in solution via LSV. First, FeCu-LIGE was placed in AP standard buffer solutions of different concentrations (0.1 M PBS, pH 7.0) at a scan rate of 0.1 V / s to obtain the AP oxidation current. As the AP concentration increased, the peak current of AP oxidation also increased accordingly. This is mainly due to the excellent conductivity, electrochemical response, specific surface area, and active sites of FeCu-LIGE, leading to increased AP adsorption and a significantly accelerated redox rate. A working curve was plotted based on the magnitude of the oxidation peak current versus the AP concentration, allowing for the quantitative detection of AP in solution. The linear range of this method was 0.05 μM ~ 0.5 mM, and the detection limit was 0.017 μM.
[0056] Example 4 The FeCu-LIGE prepared in Example 1 (prepared under conditions of 2.20 W laser power and 30% engraving depth) was used as the sensitive element of an electrochemical sensor for selective, stable, and reproducible detection. The selectivity of the FeCu-LIGE electrochemical sensor in this invention was determined using LSV (Laser-Sensitive Method). The method involved adding different interfering substances to 0.1M PBS (pH 7.0) containing 0.5mM AP, and detecting current fluctuations. The interfering substances were calcium chloride, sodium chloride, potassium chloride, magnesium chloride, sodium nitrate, sodium sulfate, nickel chloride, ascorbic acid, uric acid, and glucose, at a concentration of 2.5mM. After the addition of the interfering substances, the electrochemical response signal remained almost unchanged, indicating that the electrochemical sensor has good selectivity. Further stability testing of the FeCu-LIGE electrochemical sensor was conducted. The FeCu-LIGE was continuously stored in a vacuum drying oven at 25°C for 11 days, and LSV scans were performed every two days in a 0.5mM AP solution. After 11 days, the current value remained at 92.05% of the original current value, indicating that the modified electrode has good stability. Further reproducibility testing was conducted on the FeCu-LIGE electrochemical sensor of this invention. Seven different FeCu-LIGE electrochemical sensors were subjected to LSV scanning in 0.5 mM AP solution. The relative standard deviation (RSD) was 1.01%, indicating that the modified electrode has good reproducibility.
[0057] Example 5 The FeCu-LIGE prepared in Example 1 (FeCu-LIGE prepared under conditions of laser power of 2.20W and engraving depth of 30%) was used as the sensitive element of the electrochemical sensor for the detection of AP in actual pork and beef samples.
[0058] In this invention, FeCu-LIGE was applied to the determination of AP in actual pork and beef samples purchased from Guilin Yang Market (Haikou). According to GB29683-2013 standard, the background AP content in the pork and beef samples was undetectable before the spiked recovery test. The sample pretreatment procedure was as follows: 5.0 g of homogenized pork / beef tissue was weighed and 5.0 mL of a mixed solution of ethanol and HAc (volume ratio 1:9) was added, and the mixture was stirred vigorously for 3 minutes. The resulting supernatant was filtered through a 0.22 μm filter membrane and diluted 50 times with 0.1 M PBS buffer (pH 7.0) to obtain the test sample solution. Then, known concentrations of AP standards were added to the sample solution, and FeCu-LIGE was used to determine the AP content. The AP content in the spiked sample solution was calculated using a linear equation.
[0059] Example 6 The FeCu-LIG (prepared under conditions of 2.20W laser power and 30% engraving depth) prepared in Example 1 was used as a photocatalyst for the photocatalytic degradation of AP in water samples.
[0060] First, FeCu-LIG was immersed in 30 mL of 20 ppm AP aqueous solution to investigate its photocatalytic degradation efficiency and degradation kinetics. Then, by adding different types of trapping agents to the AP aqueous solution, the effects of each trapping agent on the photocatalytic degradation efficiency of FeCu-LIG were investigated to deduce the main active species in the reaction process. Furthermore, the effects of FeCu-LIG dosage (15–30 mg), initial AP concentration (10–40 ppm), and solution pH (3–9) on the photocatalytic degradation efficiency of AP were examined. Based on this, the recyclability of FeCu-LIG in AP degradation was investigated. Finally, FeCu-LIG was applied to AP degradation experiments in tap water and actual river water to evaluate its catalytic performance in real water bodies.
[0061] Test Example 1 Morphological and structural characterization of FeCu-LIG prepared in Example 1 Figure 1 In the image, A and B are LIG images from Example 1, and C and D are SEM images of FeCu-LIG. Figure 1 As shown in the image, a three-dimensional structure composed of porous layers was observed in both LIG and FeCu-LIG. Furthermore, the FeCu-LIG surface was modified with uniformly distributed nanoparticles. This porous structure originated from a laser-induced fabrication process, during which photothermal effects caused bond breaking and rearrangement, accompanied by rapid gas release. The resulting unique porous structure provides abundant active sites, thus facilitating the effective capture of target analytes. The uniform dispersion of the nanoparticles confirms the presence of Fe...3+ and Cu 2+ In situ, FeCu nanoparticles are uniformly distributed. Therefore, this surface modification not only expands the electrochemically active surface area and increases the density of active sites, but also enhances the wettability of the electrolyte and improves the overall electrochemical accessibility for subsequent sensing applications.
[0062] Figure 2 The XRD images of LIG and FeCu-LIG in Example 1 are shown below. Figure 2 As can be seen from the curves, both curves show characteristic peaks of graphene. In the FeCu-LIG curve, there are additional characteristic peaks of Fe and Cu, indicating the successful preparation of FeCu-LIG.
[0063] Test Example 2 According to Example 2, the electrochemical performance of LIGE and FeCu-LIGE prepared in Example 1 was studied; the electrodes were placed in a 5.0 mM [Fe(CN)6] solution containing 0.1 M KCl. 3- / 4- Redox probe solutions were tested using colorimetric chromatography (CV) in a potential range of -0.4 V to 0.8 V; the electrode was placed in a 5.0 mM [Fe(CN)6] solution containing 0.1 M KCl. 3- / 4- The redox probe solution was tested using EIS at a high frequency of 100 kHz, a low frequency of 0.01 Hz, and an amplitude of 50 mV.
[0064] Figure 3 The CV curves of FeCu-LIGE in Example 1 under different A laser powers and B engraving depths are shown below. Figure 3 It can be seen that FeCu-LIGE achieves the maximum peak current when the laser power is 2.2W and the engraving depth is 30%, which are the optimal laser parameters for FeCu-LIGE preparation.
[0065] Figure 4 The (A) CV and (B) EIS curves of LIGE and FeCu-LIGE under the optimal parameters in Example 1 are shown below. Figure 4 As can be seen from A, the peak current of FeCu-LIGE is significantly higher than that of unmodified LIGE, indicating that FeCu improves the electron transport rate at the electrode / electrolyte interface; from Figure 4 As shown in Figure B, the Rct values for LIGE and FeCu-LIGE are 1063 Ω and 657 Ω, respectively. The decrease in Rct is mainly due to the fact that the incorporation of FeCu accelerates electron transfer at the electrode surface, thereby improving conductivity.
[0066] Test Example 3 According to Example 3, the LIGE and FeCu-LIGE prepared in Example 1 were electrochemically characterized. The electrodes were placed in 0.1M PBS buffer containing 0.5mM AP and scanned using CV, with a potential range of 0V to 0.6V. FeCu-LIGE was placed in 0.1M PBS buffer containing 0.5mM AP at different pH values and scanned using LSV, with a potential range of 0V to 0.8V and a scan rate of 0.1V / s. FeCu-LIGE prepared with different amounts of FeCu-MOF was placed in 0.1M PBS (pH 7.0) buffer containing 0.5mM AP and scanned using LSV, with a potential range of 0.1V to 0.6V and a scan rate of 0.1V / s. FeCu-LIGE was placed in 0.1M PBS (pH 7.0) buffer containing different concentrations of AP and scanned using LSV, with a potential range of 0.1V to 0.6V and a scan rate of 0.1V / s.
[0067] Figure 5 The CV curves for LIGE, Fe-LIGE, Cu-LIGE, and FeCu-LIGE in 0.1M PBS buffer containing 0.5mM AP are shown in Example 1. Figure 5 It can be seen that the peak current of FeCu-LIGE is much higher than that of LIGE, Fe-LIGE and Cu-LIGE, indicating that FeCu-LIGE provides a larger electrochemical active area and better conductivity for the redox reaction of AP.
[0068] Figure 6 The following are the CV curves (A) and I²C curves (B) of FeCu-LIGE in 0.1M PBS buffer containing 0.5mM AP at different scan rates in Example 1. p and v 1 / 2 The linear relationship between them and the redox peak potential (E) corresponding to (C) p ) and ln v The linear relationship between them, from Figure 6 As can be seen from A, there is a pair of reversible redox peaks on FeCu-LIGE; from Figure 6 From B, we can see the I of AP p It increases with increasing scan rate, and I p and v 1 / 2 The linear relationship indicates that the reaction process of AP is diffusion-controlled; from Figure 6 As shown in Figure C, with the increase of scan rate, the oxidation peak potential and reduction peak potential shift in the positive and negative directions, respectively, and E... p with ln vThe two reactions exhibit a linear relationship. Based on the Laveron equation, the number of transferred electrons and the transfer coefficient were calculated to be 2.30 (≈2) and 0.51, respectively, indicating that the redox reaction of AP is a two-electron transfer process.
[0069] Figure 7 The (A) LSV curve and (B) I curve of FeCu-LIGE in 0.1M PBS buffer at different pH values containing 0.5mM AP in Example 1 are shown. p E p The relationship with pH value, from Figure 7 As can be seen from A, the peak potential shifts negatively with increasing pH, indicating that the AP oxidation process involves protons; from Figure 7 As can be seen from B, the maximum oxidation peak current occurs at pH 7.0, and the current decreases significantly at higher pH values. Therefore, PBS at pH 7.0 is determined to be the optimal buffer system. Furthermore, pH and E... p The relationship is linear, and the fitting formula is Ep(V) = -0.0506 pH + 0.715 (R²). 2 = 0.9991). The slope value of 50.6 mV / pH approximates the theoretical Nernst value (59 mV / pH), confirming that AP undergoes a two-electron coupling and two-proton transfer process (2e) in FeCu-LIGE. - / 2H + ).
[0070] Figure 8 The LSV curves of FeCu-LIGE with different FeCu-MOF doping levels in Example 1 are shown in 0.1M PBS (pH 7.0) buffer containing 0.5mM AP. Figure 8 It can be seen that when the FeCu-MOF doping concentration increases from 10 mg / mL to 30 mg / mL, the AP oxidation peak current continuously increases, while the current decreases significantly after exceeding 30 mg / mL. This phenomenon is mainly due to the aggregation effect of FeCu-MOF nanoparticles at high concentrations, leading to a reduction in electrode active sites and electron transport efficiency. Therefore, 30 mg / mL was determined to be the optimal doping concentration for FeCu-MOF modified electrodes.
[0071] Figure 9 The LSV curves (A) and (B) of FeCu-LIGE in AP solutions with gradually increasing concentrations are shown in Example 1. p The linear relationship with AP concentration, from Figure 9 As can be seen from A, with the increase of AP concentration, FeCu-LIGE I p Gradually increase; from Figure 9 From B, we can see I pThe AP concentration exhibited three linear relationships in the ranges of 0.05 μM - 7.5 μM, 7.5 μM - 100.0 μM, and 100.0 μM - 500 μM, respectively: I p-a (μA) = 2079.24C AP (mM) - 24.61 (R) 2 = 0.97955), I p-b (μA) = 1251.83C AP (mM) - 31.54 (R) 2 = 0.99463) and I p-c (μA) = 453.46C AP (mM) - 113.62 (R) 2 = 0.99095), and the detection limit is 0.017 μM.
[0072] Test Example 4 According to Example 4, the selectivity, stability, and reproducibility of the FeCu-LIGE prepared in Example 1 were studied. The selected selectivity was detected by LSV scanning in 0.1M PBS (pH 7.0) buffer containing 0.5mM AP with 2.5mM different interfering substances added. The FeCu-LIGE was stored continuously in a vacuum drying oven at 25°C for 11 days, and its stability was detected by LSV scanning in 0.5mM AP solution every two days. The reproducibility was detected by LSV scanning of 7 different FeCu-LIGE electrochemical sensors in 0.5mM AP solution.
[0073] Figure 10 The oxidation current values of FeCu-LIGE in Example 1 were obtained by adding 2.5 mM of different interfering agents to 0.1 M PBS (pH 7.0) buffer containing 0.5 mM AP. Figure 10 It can be seen that when calcium chloride, sodium chloride, potassium chloride, magnesium chloride, sodium nitrate, sodium sulfate, nickel chloride, ascorbic acid, uric acid and glucose are introduced into the system respectively, almost no electrochemical response signal is generated, indicating that FeCu-LIGE has good selectivity.
[0074] Figure 11 The oxidation current value of FeCu-LIGE in Example 1, stored continuously in a vacuum oven at 25°C for 11 days, was measured every two days in 0.1M PBS (pH 7.0) buffer containing 0.5 mMAP. Figure 11 It can be seen that the current of FeCu-LIGE remained at 92.05% of the original current after 11 days, indicating that FeCu-LIGE has good stability.
[0075] Figure 12 The oxidation current values of the seven different FeCu-LIGE roots in Example 1 in 0.1M PBS (pH 7.0) containing 0.5 mM AP are shown below. Figure 12 The RSD of 1.01% indicates that FeCu-LIGE has good reproducibility.
[0076] Test Example 5 According to Example 5, the feasibility of detecting AP content in pork and beef extract samples prepared in Example 1 was verified by spike recovery method using FeCu-LIGE diluted 50 times with 0.1M PBS buffer (pH 7.0); the electrochemical detection method used was LSV.
[0077] Figure 13 LSV curves of the FeCu-LIGE electrochemical sensor after adding different concentrations of AP to pork and beef samples diluted 50-fold; results are shown below. Figure 13 As shown, the average value of the oxidation current was read and substituted into the linear equation. The results showed that the recovery rate of the modified electrode was 98.50%-101.26% and the RSD was less than 3.37% by the spiked recovery experiment, indicating that FeCu-LIGE can be used to detect AP content in actual pork and beef samples.
[0078] Test Example 6 According to Example 6, the FeCu-LIG prepared in Example 1 was immersed in 30 mL of an AP aqueous solution with a concentration of 20 ppm to investigate its photocatalytic degradation efficiency and its degradation kinetics. Subsequently, by adding different types of capture agents (tert-butanol, disodium ethylenediaminetetraacetate, furfuryl alcohol, and hydroquinone) to the AP aqueous solution, the effect of each capture agent on the photocatalytic degradation efficiency of AP by FeCu-LIG was investigated to infer the main active species in the reaction process. Furthermore, the effects of FeCu-LIG dosage (15–30 mg), initial AP concentration (10–40 ppm), and solution pH (3–9) on the photocatalytic degradation efficiency of AP were investigated. Based on this, the recycling performance of FeCu-LIG in AP degradation was investigated. Finally, FeCu-LIG was applied to AP degradation experiments in tap water and actual river water to evaluate its catalytic performance in actual water bodies.
[0079] Figure 14 Figure A shows a comparison of the photocatalytic degradation efficiencies of LIG, Fe-LIG, Cu-LIG, and FeCu-LIG in a 30 mL aqueous solution of AP at a concentration of 20 ppm under visible light irradiation. As can be seen from the figure, FeCu-LIG exhibits the highest photocatalytic activity. Figure 14 B represents the pseudo-first-order kinetic fitting curves for the degradation of AP by four photocatalysts, and its kinetic constant (k)obs The values are LIG (0.0051 min) respectively. -1 Fe-LIG (0.0098 min) -1 Cu-LIG (0.0104 min) -1 ) and FeCu-LIG (0.0193 min) -1 The results indicate that FeCu-LIG exhibits the fastest degradation rate. These findings demonstrate that the introduction of FeCu significantly enhances the photocatalytic performance of LIG.
[0080] Figure 15 In step A, tert-butanol (TBA), disodium ethylenediaminetetraacetate (EDTA-2Na), furfuryl alcohol (FFA), and p-benzoquinone (pBQ) are added to the FeCu-LIG system as ·OH and h, respectively. + , 1 O2 and O2· - The scavenger. Results showed that in the presence of pBQ, AP degradation was almost completely inhibited, indicating that O2· - It is the main reactive species and should participate in the generation of other reactive oxygen species associated with AP degradation; Figure 15 Figure B is a schematic diagram illustrating a possible mechanism for the photocatalytic degradation of AP by FeCu-LIG. When FeCu-LIG is used as a photocatalyst, the possible pathways for the generation of active species during AP oxidation are as follows: photogenerated electrons participate in the reduction reaction of dissolved oxygen to generate O2· - This species is the main active species for AP degradation. Meanwhile, the remaining holes in the FeCu-LIG valence band can directly participate in the oxidative degradation of organic pollutants, react with water molecules to generate highly reactive ·OH, and further react with O2· - Reaction generation 1 O2. The synergistic effect of the above-mentioned active species decomposes organic pollutants into small-molecule, low-toxicity products, playing a key role in the degradation process.
[0081] Figure 16 The effect of FeCu-LIG dosage (15–30 mg) on the photocatalytic degradation efficiency of AP was investigated. With increasing dosage, the AP removal rate gradually increased, attributed to the increase in light area and active sites; at a dosage of 25 mg, the degradation rate reached 87.43% within 60 min. Further increasing the dosage may lead to particle agglomeration, inhibiting light absorption and decreasing the degradation efficiency. Figure 16 The effect of initial AP concentration (10–40 ppm) on photocatalytic degradation was investigated in section B. At 10 ppm, AP could be completely degraded within 60 min; at 40 ppm, the degradation rate decreased to 45.18%, which was attributed to the limited number of active sites on the catalyst and competitive adsorption by intermediate products. Figure 16The effect of different pH values (3–9) on the photocatalytic degradation of AP was evaluated. The degradation rate increased with decreasing pH, mainly due to the fact that FeCu-LIG is more readily protonated under acidic conditions, which enhances the adsorption between the catalyst and AP.
[0082] Figure 17 The photocatalytic degradation performance of FeCu-LIG under optimal conditions after five cycles is shown. After five cycles, the AP degradation efficiency remains above 70%, indicating that the catalyst has good reusability. The slight decrease in FeCu-LIG activity after the first cycle is attributed to the blockage of active sites by AP degradation intermediates.
[0083] Figure 18 The degradation effect of FeCu-LIG on AP in deionized water, tap water, and river water is shown. The degradation rate is the highest in deionized water. The reaction rate decreases in actual water samples (tap water and river water), which is attributed to the competitive consumption of active species by components such as ions and organic matter in the water matrix, thereby inhibiting the reaction kinetics.
[0084] Comparative Example 1 The only difference from Example 1 is that FeCu-MOF is replaced with Fe-MOF in step (1); the other steps and parameters are the same as in Example 1. The modified electrode obtained is denoted as Fe-LIGE.
[0085] Results: The modified electrode prepared in this comparative example was subjected to the same tests as in Example 1. The results showed that the modified electrode prepared in this comparative example had a detection limit of 0.33 μM for AP, a linear range of 1.0 μM ~ 200 μM, and the stability test showed that its current remained at 83.5% of the original current after 11 days.
[0086] Comparative Example 2 The only difference from Example 1 is that FeCu-MOF is replaced with Cu-MOF in step (1); the other steps and parameters are the same as in Example 1. The modified electrode obtained is denoted as Cu-LIGE.
[0087] Results: The modified electrode prepared in this comparative example was subjected to the same tests as in Example 1. The results showed that the modified electrode prepared in this comparative example had a detection limit of 0.17 μM for AP, a linear range of 0.5 μM to 300 μM, and the stability test showed that its current remained at 78.2% of the original current after 11 days.
[0088] Comparative Example 3 FeCu-MOF was dispersed in ethanol to form a dispersion with a concentration of 30 mg FeCu-MOF. Nafion solution was then added dropwise to this dispersion to achieve a final Nafion concentration of 1 mg / mL. -1The purpose is to enable the dispersion to form an electrode film on the electrode surface and avoid the detachment of the modification material during the test. The above dispersion is applied to the surface of LIGE (the preparation method of LIGE is the same as that of LIGE in Example 1) by using a pipette in a drop-coating method, and then dried in an infrared drying oven to obtain the modified electrode.
[0089] Results: The modified electrode prepared in this comparative example was subjected to the same tests as in Example 1. The results showed that the modified electrode prepared in this comparative example had a detection limit of 0.67 μM for AP, a linear range of 2.0 μM ~ 150 μM, and the stability test showed that its current remained at 73.2% of the original current after 11 days.
[0090] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing an iron-copper co-doped graphene composite material, characterized in that, Includes the following steps: FeCu-MOF was dispersed in an organic solvent to obtain a dispersion; The dispersion was mixed with liquid polyimide and then coated onto the substrate surface, followed by curing to obtain a flexible precursor film. The flexible precursor film was subjected to laser-induced treatment to obtain the iron-copper co-doped graphene composite material.
2. The preparation method according to claim 1, characterized in that, The organic solvent is ethanol; the concentration of FeCu-MOF in the dispersion is 5-50 mg / mL; the ratio of the dispersion to liquid polyimide is 200 μL: 4 g.
3. The preparation method according to claim 1, characterized in that, The curing process is carried out at a temperature of 80~100℃ for 20~30 minutes.
4. The preparation method according to claim 1, characterized in that, The parameters for the laser-induced processing are set as follows: wavelength 450nm, laser power 1.38~2.48W, and engraving depth 15%~35%.
5. A copper-iron co-doped graphene composite material prepared by the preparation method according to any one of claims 1-4.
6. The application of the iron-copper co-doped graphene composite material of claim 5 in the photocatalytic degradation of acetaminophen.
7. A modified electrode, characterized in that, The electrode modification material is the iron-copper co-doped graphene composite material as described in claim 5.
8. An electrochemical sensor, characterized in that, Includes the modified electrode as described in claim 7.
9. The application of the iron-copper co-doped graphene composite material of claim 5, the modified electrode of claim 7, or the electrochemical sensor of claim 5 in the detection of acetaminophen.